Low Birth Weight and Attention Deficit Disorder - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The relation of low birth weight to the risk of attention deficit hyperactivity disorder was determined in a population-based sample of 1,480 twin pairs ascertained from the Swedish twin registry in the period 1985-1986.